Desigualdades nas condições de aprendizado em escolas públicas municipais de São Luís-Maranhão: um estudo de caso - Flávia Fernanda Santos Silva (2016)
Since the 1960s, the sociological literature has registered that the socioeconomic background and the culture of the families of students may explain most of the inequalities in school performance. Since 1970, studies of educational institutions questioned such determinism while emphasizing that school factors shoud not be neglected. In Brazil, these studies are more recent and the national results corroborates these last conclusions. . The interest of this research came about on the questioning over the negative results of the state of Maranhão in the large-scale assessments, a fact which is presented as in opposite direction of the improving trend seen in most Brazilian states including those with similar socio-economic context in the same region of the country. The objective of this dissertation is to investigate school factors where a large portion of students cannot achieve adequate learning for school stage they are in. Based on the educational literature and the local reality, some factors associated with schools that could explain this phenomenon were highlighted. This research investigated the following factors: infrastructure, resources, teacher training, pedagogical policies and curriculum. Two municipal schools from the city of São Luís were investigated, selected through statistical models that control the socioeconomic status of students and that enable the identification of schools that have positive and negative effects on the average estimate of schools in the country. In these schools studies of comparative case were carried out, by using secondary data from schools that are available for public access, as well as the observation and the interviews with teachers who teach subjects (Portuguese Language and Mathematics) and grades assessed by Test Brazil (5th and 9th grade), coordinators and managers of schools. The results show that teachers who performs in the assessed area have appropriate qualification. On spite of this, the schools have many failures regarding infra-structure items which are real obstacles to the educational processes. The existence of school units called "attachments" with even more precarious service conditions are seen by the individuals of the schools, as harmful to the learning process and working conditions of teachers. It was observed that they consider that the implementation of the curriculum has been harmed, and students do not have access to essential knowledge, a situation that has been revealed in the results of the trial Brazil. This research has contributed for the strengthening of the educational researches over the effect of the school once it highlights how statistical evidences are set in the day by day of the Educational Institutions. The results above illustrate the association / resources and devaluation of the learning and curriculum by the public administration, which results in official negative indicators of the state.